Survey of Income and Program Participation (SIPP) 2004 Panel ([Verlag nicht ermittelbar], 2009)
This data collection is part of a longitudinal survey designed to provide detailed information on the economic situation of households and persons in the United States. These data examine the distribution of income, wealth, and poverty in American society and gauge the effects of federal and state programs on the well-being of families and individuals. There are three basic elements contained in the survey. The first is a control card that records basic social and demographic characteristics for each person in a household, as well as changes in such characteristics over the course of the interviewing period. These include age, sex, race, ethnic origin, marital status, household relationship, education, and veteran status. Limited data are provided on housing unit characteristics such as the number of units in the structure, tenure, access, and complete kitchen facilities. The second element is the core portion of the questionnaire, with questions repeated at each interview on labor force activity, types and amounts of income, and participation in various cash and noncash benefit programs for each month of the four-month reference period. Data for employed persons include number of hours and weeks worked, earnings, and weeks without a job. Nonworkers are classified as unemployed or not in the labor force. In addition to providing income data associated with labor force activity, the core questions cover nearly 50 other types of income. Core data also include postsecondary school attendance, public or private subsidized rental housing, low-income energy assistance, and school breakfast and lunch participation. The third element consists of topical modules, which are a series of supplemental questions asked during selected household visits. Topical modules include some core data to link individuals to the core files. For more information on this study, see the SIPP Web site. Information about child care is located in the topical modules for Waves III, V, VI, and VIII. The Wave I Topical Module covers recipiency and employment history. The Wave II Topical Module includes work disability, education and training, household relationships, marital, migration, and fertility histories. The Wave III Topical Module covers medical expenses and utilization of health care, work-related expenses and child support, assets and liabilities, real estate, shelter costs, dependent care, vehicles, value of business, interest earning accounts, rental properties, stocks and mutual fund shares, mortgages, other assets, and child well-being. The Wave IV Topical Module covers adult well-being, work schedule, taxes, child care, and annual income and retirement accounts. Data in the Wave V Topical Module describe child support agreements, school enrollment and financing, support for nonhousehold members, adult and child disability, and employer-provided health benefits. The Wave VI Topical Module covers medical expenses and utilization of health care, work-related expenses, child support paid and child care, poverty, assets and liabilities, real estate, shelter costs, dependent care, vehicles, value of business, interest earning accounts, rental properties, stock and mutual fund shares, mortgages, and other financial investments. The Wave VII Topical Module covers retirement, pension plan coverage, annual income, taxes, and retirement accounts. Variables on informal caregiving, such as who received unpaid care and how long they were cared for, are located in a separate topical module file. The Wave VIII Topical Module covers welfare reform, child well-being, and child care.